Agustín, buscador en compañía - Pascual, L.C., Fernando (Alpha Omega, 2017)
Summary: The present article develops a synthesis of different ideas of St. Augustine about dialogue and human education, on the basis of five works of the Bishop of Hippo, giving special attention to his statements about the way in which the one who is speaking and the one who is listening should relate to each other.Sommario: Il presente articolo elabora una sintesi di diverse idee di Sant’Agostino sul dialogo e l’educazione umana, a partire da 5 opere dal vescovo d’Ippona, con speciale riguardo alle sue dichiarazioni circa il modo di rapportarsi tra chi parla e chi ascolta.Key words: Augustine, education, theory of dialogue, authority.Parole chiave: Agostino, educazione, dialogo, autorità.